Verstípus és stílustörténet: a magyar tájlíra három változata: (Keszthely, Az alföld, Nádas tavon) - S. Varga, Pál (Studia Litteraria, 2019)
Topographical poetry is the characteristic lyrical text group of 19th century Hungarian literature; its history illustrates the impact of the contemporary style and norms defining the creation and reception of literary works and its changes on the formation of certain types of poems. In the background of the poem titled “Keszthely” and written by Dániel Berzsenyi between 1799 and 1803 we can discover the classicistic natural theory, supported by Descartes’s anthropological dualism, in which the distinction between Nature and Culture is essential; this gives the basis in the poem to identify the picturesque and agriculturally rich area around Lake Balaton with Helicon, the home of the Muses. Sándor Petőfi’s poem, “Az alföld” (“The Great Plain”) (1844) follows the unity theory of romantic anthropology and it uses the expansionist human model of romanticism. The poem presupposes the innate relationship of landscape and Self: the narrator loves his native land, the Great Plain with endless possibilities, because he received his fundamental characteristic from it, the desire for freedom. The poem “Nádas Tavon” (“On a Lake with Reed”) (1888) by János Vajda preserves the romantic relationship between the landscape and the Self but it renounces the interpretation of this relationship and by that it realises the limitations of poetic language.